Process measurement series - Coastal Training Technologies Corporation; Instrumentation, Systems and Automation Society; Clarity Multimedia (Virginia : Coastal Training Technologies, 2001)
This eight-part series is designed to familiarize the viewer with temperature, pressure, level and flow measurement. The program details the principles of each and identifies the equipment for measuring each component
pt.1. Temp: thermometers and thermocouples - pt. 2. Temp: resistance and radiation devices - pt. 3. Pressure: manometers and gages - pt. 4. Pressure: indicators and transmitters - pt. 5. Level: level measurement and gages - pt. 6. Level: level indicators and transmitters - pt. 7. Flow: flow measurement overview - pt. 8. Flow: flow sensors
Title from container
CD-ROM Format
Keywords: Temperature measuring instruments; Temperature measurements; Thermometers; Resistance thermometers; Pressure -- Measurement -- Instruments; Pressure gages; Manometers; Level indicators; Flow meters; Rotameters; Thermocouples